Advertising, Trust and Commitment to Customer Loyalty to a Technology Company from Indonesia that Serves Ojek Services in Sidoarjo: Iklan, Kepercayaan dan Komitmen Terhadap Loyalitas Pelanggan pada Perusahaan Teknologi Asal Indonesia Yang Melayani Jasa Ojek di Sidoarjo - Ulfah, Maria; Indahyani, Lilik (Universitas Muhammadiyah Sidoarjo, 2023)
This research is a type of quantitative research with hypothesis testing. The sample used in this study as many as 100 respondents, namely customers who use the services of Gojek. The sampling technique used the accidental sampling method. The analytical tools used in this research are multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, f test, and classical assumption test using SPSS version 18.0 application program. The data used in this study are questionnaire data and data sourced from customers who use Gojek's services. Data collection techniques using questionnaires.